Malaria incidence and prevalence during the first year of life in Nanoro, Burkina Faso: a birth-cohort study - Hamtandi Magloire Natama; Eduard Rovira-Vallbona; M. Athanase Somé; Serge Henri Zango; Hermann Sorgho; Pieter Guetens; Maminata Coulibaly-Traoré; Innocent Valea; Petra F. Mens; Henk D. F. H. Schallig; Luc Kestens; Halidou Tinto; et al. (Malaria Journal, 2018)
Abstract Background Infants are thought to be protected against malaria during the first months of life mainly due to passage of maternal antibodies. However, in high transmission settings, malaria in early infancy is not uncommon and susceptibility to the infections varies between individuals. This study aimed to determine malaria morbidity and infection during early childhood in rural Burkina Faso. Methods Malariometric indices were determined over 1-year follow-up in a birth cohort of 734 infants living in Nanoro health district. Clinical malaria episodes were determined by passive case detection at peripheral health centres while asymptomatic malaria infections were identified during 4 cross-sectional surveys at 3, 6, 9 and 12 months of age. Plasmodium falciparum infections were detected by rapid diagnostic test and/or light microscopy (LM) and quantitative PCR (qPCR). Results In total, 717 clinical episodes were diagnosed by qPCR over 8335.18 person-months at risk. The overall malaria incidence was 1.03 per child-year and increased from 0.27 per child-year at 0–3 months of age to 1.92 per child-year at 9–12 months of age. Some 59% of children experienced at least one clinical episode with a median survival time estimated at 9.9 months, while 20% of infants experienced the first episode before 6 months of age. The majority of the clinical episodes were attributable to microscopic parasitaemia (84.2%), and there was a positive correlation between parasite density and age (Spearman’s rho = 0.30; P < 0.0001). Prevalence of asymptomatic infections was similar at 3, 6 and 9 months of age (17.7–20.1%) and nearly 1.6 times higher at 12 months (31.3%). Importantly, gametocyte prevalence among the LM-positive study population was 6.7%, but increased to 10% among asymptomatic infections. In addition, 46% of asymptomatic infections were only detected by qPCR suggesting that infants below 1 year are a potential reservoir for sustaining malaria transmission. Both symptomatic and asymptomatic infections showed marked ...